1993
DOI: 10.2527/1993.71102815x
|View full text |Cite
|
Sign up to set email alerts
|

A review of behavioral factors involved in the development and continued performance of stereotypic behaviors in pigs

Abstract: Environmentally induced stereotypies, commonly observed in farm and zoo animals, are behaviors that are relatively invariant, that are regularly repeated, and that serve no obvious function. However, there is as yet no accepted means of discriminating between normal and abnormal behavior, and the assumption that stereotypies are abnormal may mask the fact that they arise in part through processes that "normally" control behavior. There is growing evidence that stereotypies in sows and broiler breeders are stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(101 citation statements)
references
References 36 publications
3
97
0
1
Order By: Relevance
“…Sham chewing and other non-feeding oral activities were classified as stereotypical behaviour, and sham chewing is most likely the most detrimental stereotypy because it is considered to be in a more advanced stage of development (Stolba et al, 1983;Lawrence and Terlouw, 1993;VieuilleThomas et al, 1995). Stereotypical behaviour was mainly performed during 2 h following feeding, and it is always higher in the stalls (Jensen, 1988;Chapinal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sham chewing and other non-feeding oral activities were classified as stereotypical behaviour, and sham chewing is most likely the most detrimental stereotypy because it is considered to be in a more advanced stage of development (Stolba et al, 1983;Lawrence and Terlouw, 1993;VieuilleThomas et al, 1995). Stereotypical behaviour was mainly performed during 2 h following feeding, and it is always higher in the stalls (Jensen, 1988;Chapinal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lawrence and Terlouw ( 1993) suggested that food restriction and the inability to express resulting foraging behaviour is one of the main causes for the development of stereotypies in sows. They argue that in food-restricted sows the positive feedback effects of feeding in the early stages of a meal (Wiepkema,197 1) overrules the negative feedback from ingestion of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…This 'channelling' of complex behaviour into a few repeated sequences could be an important prerequisite stage in the sensitisation of underlying neural elements (Dantzer, 1986)) which would allow stereotypies to be more easily elicited and maintained. Lawrence and Terlouw (1993) hypothesise that there are two methods of preventing stereotypies from developing: by reducing the level of feeding motivation, or by allowing the expression of more complex behaviours to prevent the channelling process. The present study was designed to investigate this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, we used a reward that had great incentive value because it was highly palatable and because our sows were fed at commercial feed levels, which satisfy only about 40% to 60% of their ad libitum feed intake (Brouns et al, 1995;Meunier-Salaün et al, 2001). Such commercial feeding levels are known to leave sows hungry (Lawrence et al, 1988;Lawrence and Terlouw, 1993). Both feed deprivation (Robert et al, 1997;Patterson-Kane et al, 2011) and good palatability (Baldwin, 1976) are known to increase feeding motivation in sows.…”
Section: Discussionmentioning
confidence: 99%